Endoscopic findings of acute upper gastrointestinal bleeding in a tertiary care hospital - Sharma, Yuba Raj; Shah, Jay N (Journal of Patan Academy of Health Sciences, 2015)
Introduction: Acute upper gastrointestinal (UGI) bleeding is a common emergency. Prompt endoscopic diagnosis has an important role in overall management of patients. This study analyses the endoscopic findings of UGI bleeding in a tertiary care teaching hospital. Methods: This was a cross sectional study of patients with haematemesis, melaena or both who had UGI endoscopy at Patan Hospital during Nov 2009 to Dec 2010. Patient demographics, site and nature of lesions and risk factors for bleeding were analyzed. Results: There were 301 patients, male 203 (67%) female 98 (33%), age 15 to 92 years. Esophageal lesions were seen in 136 (45%), gastric 102 (34%), duodenal 46 (15%) and unidentified in 17 (7%). The lesions detected were esophageal varices in 120 (40%), duodenal ulcer in 32 (11%), Mallory-Weiss tear in 26 (9%), gastric ulcer in 18 (6%), gastric carcinoma in 17 (6%) and congestive pan-gastropathy in 16 (5%). History of drugs intake like aspirin, nonsteroidal anti-inflammatory drugs, warfarin and bisphosphonates was present in 32 (11%) patients. Conclusions: Endoscopy was diagnostic in majority (94% of 301) UGI bleeding patients. Esophageal variceal bleeding was the common cause followed by peptic ulcer. Journal of Patan Academy of Health Sciences, Vol. 2, No. 1, 2015. page: 22-25